Uma abordagem gravitacional da evolução do comércio potencial entre o Brasil e parceiros asiáticos selecionados - Bampi, Sílvia Letícia (Universidade do Vale do Rio dos Sinos, 2017)
International trade has shown more growth than the domestic product of the nations. Globalization of economies coupled with the rise of Asian economies to international trade has altered the patterns of consumption of industrialized economies, causing the trade international structure to change. Then, in order to verify the possibility the Brazil's trade expansion along with the Asian economies, given the probability of increasing its growth and reducing protectionist practices, the present study tried to estimate the potential trade of the Asian continent with Brazil from 2000 to 2014. For this purpose, the gravitational equation was used through panel data and fixed effects and a sample of 74 countries. The estimates have identified that there are significant possibilities of expansion with relation to the trade between of Brazilian and Asia, mainly when it comes to exports, which would represent an increase of U$ 22,540 million. For this reason it is important to emphasize the possibility of expanding the Brazil's export flow between Brazil and Philippines as well as Brazil and China and Brazil and South Korea, at 313.57% (US$ 538 million), 36.99% (US$ 19,115 million) and 33.63% (U$$ 1,650 million), respectively. Besides each of the latter, Thailand, Singapore and Malaysia also showed a trade potential which was over the real flow. In the years herein studied, the Brazilian potential imports towards these economies were lower than the real ones.
Keywords: Comércio internacional; Modelo gravitacional; Ásia; Brasil; International trade; Gravity model; ACCNPQ::Ciências Sociais Aplicadas::Economia